In silico identification of antidiabetic target for phytochemicals of A. marmelos and mechanistic insights by molecular dynamics simulations. Issue 21 (5th December 2022) - Sharma, Priyanka; Joshi, Tushar; Mathpal, Shalini; Chandra, Subhash; Tamta, Sushma
Abstract: The leaves and fruits of Aegle marmelos (L.) have antidiabetic activity. However, the mode of action and molecules having antidiabetic activity are not known. Hence, we conducted molecular docking of phytochemicals with various molecular antidiabetic targets to find the same. Docking prioritized Dipeptidyl peptidase-4 (DPP-4) as the main target for phytochemicals of Aegle marmelos . DPP-4 inactivates intestinal peptides, glucagon-like peptide-1 (GLP-1), and Gastric inhibitory polypeptide (GIP). GLP-1 and GIP stimulate a decline in blood glucose levels, but DPP-4 inhibits their functions resulting high level of glucose. Hence inhibiting the activity of DPP-4 is a well-known strategy to treat Type 2 diabetes. Therefore, to find a mechanism that may be involved to act as a natural inhibitor of DPP-4, we screened five phytochemicals out of seventy-three based on Virtual Screening, ADMET Drug-likeness analysis, and PAINS filtering. Further, all five phytochemicals, i.e. Aegeline, Citral, Marmesinin, Auraptene, β-Bisabolene, and reference compound subjected MDS for analyzing the stability of docked complexes to assess the fluctuation and conformational changes during protein-ligand interaction. The values of RMSD, RG, RMSF, SASA, and Gibbs energy revealed the good stability of these phytochemicals in the active site pocket of DPP-4 in comparison to reference. Additionally, we have done the pharmacophore analysis, which revealed many common pharmacophore features between screened phytochemicals of A. marmelos and reference molecule. Our results show that these phytochemicals are potential antidiabetic candidates and can be further modified and evaluated to develop more effective antidiabetic drugs against DPP-4 to treat Type 2 Diabetes. Communicated by Ramaswamy H. Sarma